Learning Innovations in the Implementation of Social Distancing Policies in the Covid-19 Pandemic: University Students’ Perception - Candra Wijaya; Ilwan Mardani; Muhammad Nasir; Ishak Ishak; Ahmad Yani (AL-ISHLAH: Jurnal Pendidikan, 2021)
This paper aims to analyze student perceptions of social distancing in education in the Covid-19 pandemic in the context of educational innovation. The focus of the discussion in this study is how students perceive social distancing in education in the Covid-19 pandemic and the learning patterns applied during the COVID-19 pandemic at the university in Labuhanbatu Utara. This research uses a qualitative approach with a case study method. The data collection techniques are structured interviews with informants (students and lecturers), observation and document study. Furthermore, the data were analyzed using data reduction techniques, descriptive data presentation and concluding. The results of this study indicate that students' perceptions of social distancing in education are a temporary policy issued by the government to anticipate the spread of the Covid-19 virus. On this basis, educational institutions (especially universities) apply online learning using the WhatsApp Group (WAG) application, and Zoom Meeting. The main purpose of using online media is as an alternative for learning, assignment and assessment of lectures during the Covid-19 pandemic.